(3OQQ GdMcGe aj TQM ZQQ GdCMcGes - (3edG NSQh, eMeO Hf aQGehR Hf Ydj, J (B885 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CMce CMcGe GdTQY hHYO aEf GdebOeGJ GdebQQI YfO Chdj GdCHUGQ hgh Yde Gdabg hQGYjJ eG PcQJ ef CfUGa GdeJf HGdUaGJ GdePchQI hYReJ Cf CSejJg HZQQ GdCMcGe s
(3BNQgG (B:s
(3dCf GdhUj dh YRe Ydi JQc GdNUheI cGf aSNgeG HefRdI GdEbGdI ajdRe GdhUj cdeG dh JbGHdG MbjbI aEPG aSN GdbGVj de jcf EbGdI adG jdRe GdhUjs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B883 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 328s
(3eYLe GdeDdajf (B3 / 584s
(3cTa GdXfhf (B2 / 1199s
(3TPQGJ GdPgH (B7 / 342s
Keywords: (3Gdabg GdMfHdjs